Implementasi Program cashless dalam Membentuk Karakter Iffah Santri di Pondok Pesanteren Assalafie Babakan Ciwaringin Cirebon (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
The development of digital technology has encouraged the adoption of a cashless society system by various educational institutions, including Islamic boarding schools (pesantren). This study aims to analyze the implementation of the cashless program and its contribution to the development of the iffah character of students at the Assalafie Babakan Ciwaringin Islamic Boarding School in Cirebon. The study used a descriptive qualitative approach with data collection techniques through in-depth interviews, participant observation, and documentation. Research informants consisted of caretakers, Islamic boarding school administrators, and students involved in the implementation of the cashless program. Data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results show that the cashless program is implemented through the use of digital cards for various transactions in Islamic boarding school business units, such as cooperatives, canteens, and book stores. The implementation of this program not only improves the efficiency of financial management and minimizes the risk of loss of money but also contributes to the development of the iffah character of students. Through balance management and spending restrictions, students are accustomed to controlling consumptive behavior, distinguishing between needs and wants, and developing attitudes of discipline, thrift, trustworthiness, and responsibility. Thus, the cashless program functions not only as a financial service innovation, but also as a character education medium that supports the internalization of Islamic values ​​in the digital era.